2019
DOI: 10.5004/dwt.2019.24043
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-assisted removal of inorganic scales in high-salinity wastewater treatment using membrane distillation

Abstract: This study focuses on ultrasonic-assisted cleaning of MD membranes for the treatment of high-TDS feed waters. The conditions for the ultrasonic application were explored to increase the cleaning efficiency and to minimize physical damage to the membrane. MD fouling tests were performed using synthetic feed waters with high scaling potential. After the fouling tests, cleaning experiments were performed by immersing the membrane cell in an ultrasonic generator and operated with a citric acid solution. The recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Their study also stated that the ratio of the permeate flux with ultrasound to that with zero ultrasound can be expanded. Cho et al [ 88 ] employed ultrasonic cleaning on fouled membranes, and they observed that it is more effective in eliminating membrane foulants and regaining the flux comparison with conventional physical and chemical cleaning techniques. However, the authors reported structural damage to the membranes when the use of elevated ultrasonic power at low frequencies (150 and 300 W at 28 and 45 kHz).…”
Section: Strategies For Curtailing Membrane Fouling To Enhance the Fr...mentioning
confidence: 99%
“…Their study also stated that the ratio of the permeate flux with ultrasound to that with zero ultrasound can be expanded. Cho et al [ 88 ] employed ultrasonic cleaning on fouled membranes, and they observed that it is more effective in eliminating membrane foulants and regaining the flux comparison with conventional physical and chemical cleaning techniques. However, the authors reported structural damage to the membranes when the use of elevated ultrasonic power at low frequencies (150 and 300 W at 28 and 45 kHz).…”
Section: Strategies For Curtailing Membrane Fouling To Enhance the Fr...mentioning
confidence: 99%
“…The technique of sessile drop contact angle measurement was applied to the fabricated membranes as previously reported [11,40]. An instrument to measure the contact angle (Smart Drop) was supplied by Femtobiomed (Gyeonggi-do, Korea).…”
Section: Contact Angle (Ca) Measurementmentioning
confidence: 99%
“…An in-house apparatus was used to measure the liquid entry pressure (LEP) of the fabricated membranes [11,40]. As shown in Figure 1, the apparatus consists of an LEP chamber, a pressure gauge, a high-pressure N 2 gas cylinder, and a pipe.…”
Section: Measurement Of Liquid Entry Pressurementioning
confidence: 99%
See 2 more Smart Citations